2016
DOI: 10.1002/adma.201604989
|View full text |Cite
|
Sign up to set email alerts
|

In‐Plane Deformation Mechanics for Highly Stretchable Electronics

Abstract: Stretchable electronics represents a relatively recent class of technology [1,2] of interest partly due to its potential for applications in sensory robotic skins, [3,4] conformal photovoltaic modules, [5,6] wearable communication devices, [7,8] skin-mounted monitors of physiological health, [9][10][11] advanced, soft surgical and clinical diagnostic tools, [11,12] and bioinspired digital cameras. [13,14] A key challenge in each of these systems is in the development of strategies in mechanics that simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
132
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 37 publications
1
132
0
1
Order By: Relevance
“…Recently, Su et al 42 introduced a different route to stretchable structures, where thick bar geometries replace thin ribbon layouts, to yield scissor-like deformations instead of in-plane or out-ofplane buckling modes. In their systematic theoretical, numerical, and experimental studies, it was observed that three different buckling modes exist for serpentine interconnects consisting of both straight and curved segments, as the thickness of interconnects increases from tens of nanometers to~100 μm.…”
Section: Suppressing Buckling Behaviors With Thick Interconnects For mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Su et al 42 introduced a different route to stretchable structures, where thick bar geometries replace thin ribbon layouts, to yield scissor-like deformations instead of in-plane or out-ofplane buckling modes. In their systematic theoretical, numerical, and experimental studies, it was observed that three different buckling modes exist for serpentine interconnects consisting of both straight and curved segments, as the thickness of interconnects increases from tens of nanometers to~100 μm.…”
Section: Suppressing Buckling Behaviors With Thick Interconnects For mentioning
confidence: 99%
“…With optimum designs, the scissoring mechanism can be exploited to increase elastic stretchability (defined as maximum cyclic stretching level that does not cause fracture) to~350%, which represents a sixfold enhancement than previously reported values (about 60%). 43 Su et al 42 analyzed the three buckling modes from the energy perspectives, and obtained analytically the criteria to separate the three different buckling modes:…”
Section: Suppressing Buckling Behaviors With Thick Interconnects For mentioning
confidence: 99%
“…The ability to program the mechanical response of materials and structures is enabling a wide set of innovative applications ranging from stretchable electronics and wearable devices [1,2] to soft robots [3][4][5][6][7] and drug delivery systems. [8,9] Recently, kirigami-the Japanese art of paper cutting-has been identified as a powerful tool to realize programmable mechanical metamaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional flexible electronics are bendable devices where the substrate has a reduced thicknesses, laminated with metal interconnects to reduce the strain change due to bending. For the emerging stretchable/super-flexible devices [1][2][3][4], substrate deformation strain could be much higher than the fracture strains of rigid materials during compressing and stretching. To avoid compromising local features such as metal interconnects and integrated transducers, different strategies have been developed, such as island-bridge and serpentine shaped interconnects [1,5] and competing growth of elastic instabilities [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Bendable and stretchable sensor and actuator technologies based on soft functional materials have become ever popular with emerging applications such as epidermal electronics, artificial skins, and soft robotics [1][2][3][4]. Conventional flexible electronics are bendable devices where the substrate has a reduced thicknesses, laminated with metal interconnects to reduce the strain change due to bending.…”
Section: Introductionmentioning
confidence: 99%